ANALISIS SENTRA IKM ANYAMAN BAMBU DAN ROTAN SEBAGAI PENOPANG EKONOMI KELUARGA DUSUN KENANAI - Ira, Ira; Mashudi, Mashudi; Asriati, Nuraini (Universitas Tanjungpura, 2024)
The purpose of this study was to determine how the results of bamboo and rattan weaving in Kenanai Hamlet can support the family economy of the craftsmen community in Kenanai Hamlet, Sambas Regency. This study uses a descriptive qualitative approach. The data collection techniques used in this study are using three methods, namely observation, interviews, and documentation. Using data analysis techniques, namely data reduction, data presentation, and drawing conclusions and verification. The data validity checking technique in this study uses triangulation and reference materials. The data sources for this study were the Head of Kenanai Hamlet and bamboo and rattan weaving craftsmen. The results of the study showed that there were several products produced, namely rattan parabolic chairs, clothes racks, rattan plates, fruit baskets, nyiru, food covers, pen holders and rocking horses and trash baskets. The results of the sale of bamboo and rattan woven products can support the family economy, including the fulfillment of primary needs, increasing income, and absorbing labor.